Enhancing viability and angiogenic efficacy of mesenchymal stem cells via HSP90α and HSP27 regulation based on ROS stimulation for wound healing - Inwoo Seo; Sung‐Won Kim; Jiyu Hyun; Yu‐Jin Kim; Hyun Su Park; Jeong‐Kee Yoon; Suk Ho Bhang (Wiley, 2023)
Abstract Light‐based therapy has been reported as a potential preconditioning strategy to induce intracellular reactive oxygen species (ROS) signaling and improve the angiogenic properties of various types of cells. However, bio‐stimulation mechanisms of light therapy in terms of ROS‐heat shock proteins (HSPs) mediated anti‐apoptotic and angiogenic pathways in human adult stem cells have not been fully delineated yet. Commonly used light sources such as light‐emitting diode (LED) and laser are accompanied by drawbacks, such as phototoxicity, thermal damage, and excessive ROS induction, so the role and clinical implications of light‐induced HSPs need to be investigated using a heat‐independent light source. Here, we introduced organic LED (OLED) at 610 nm wavelength as a new light source to prevent thermal effects from interfering with the expression of HSPs. Our results showed that light therapy using OLED significantly upregulated anti‐apoptotic and angiogenic factors in human bone marrow mesenchymal stem cells (hMSCs) at both gene and protein levels via the activation of HSP90α and HSP27, which were stimulated by ROS. In a mouse wound‐closing model, rapid recovery and improved re‐epithelization were observed in the light‐treated hMSCs transplant group. This study demonstrates that the upregulation of Akt (protein kinase B)‐nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) signaling, caused by HSP90α and HSP27 expression, is the mechanism behind the anti‐apoptotic and angiogenic effects of OLED treatment on stem cells.